Management of Juvenile Polyposis Syndrome in Children and Adolescents: A Position Paper From the ESPGHAN Polyposis Working Group. Issue 3 (March 2019) - Cohen, Shlomi; Hyer, Warren; Mas, Emmanuel; Auth, Marcus; Attard, Thomas M.; Spalinger, Johannes; Latchford, Andrew; Durno, Carol
Abstract : ABSTRACT: The European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) Polyposis Working Group developed recommendations to assist clinicians and health care providers with appropriate management of patients with juvenile polyposis. This is the first juvenile polyposis Position Paper published by ESPGHAN with invited experts. Many of the published studies were descriptive and/or retrospective in nature, consequently after incorporating a modified version of the GRADE system many of the recommendations are based on expert opinion. This ESPGHAN Position Paper provides a guide for diagnosis, assessment, and management of juvenile polyposis syndrome in children and adolescents, and will be helpful in the appropriate management and timing of procedures in children and adolescents. The formation of international collaboration and consortia is proposed to monitor patients prospectively to advance our understanding of juvenile polyposis conditions.